Neonatal encephalopathy in Aotearoa New Zealand: a review utilising two existing population datasets - Malcolm R. Battin; Lynn Sadler; Jutta van den Boom (Frontiers in Pediatrics)
IntroductionIn Aotearoa New Zealand, the Perinatal & Maternal Mortality Review Committee (PMMRC) collects national data on moderate/severe neonatal encephalopathy (NE), including demographic and clinical details, such as treatment with therapeutic hypothermia (TH). The Australian and New Zealand Neonatal Network (ANZNN) collects data on infants who receive TH. However, for ANZNN, receipt of TH is the entry criteria, not severity of NE or gestation. As these datasets have different entry criteria, there is potential to combine and gain greater insight into treatment provided nationally for NE.MethodsThe specific objectives were (1) to compare the NE dataset collected by the PMMRC and the ANZNN cooling dataset from all level 2 and 3 neonatal intensive care units (NICUs) in NZ to understand differences, including the ability to estimate rates of NE over time; (2) to review temporal trends in the provision of TH nationally in NZ over the 9-year period (2010–2018), including documenting the number/year in both datasets and between centre variations; and (3) to assess receipt of TH for NZ infants with moderate to severe NE to ensure it was appropriate and equitable across all groups. The ANZNN dataset is collected in a de-identified manner so analysis was at the aggregate (i.e., total national and/or tertiary NICU) not individual level.ResultsA total of 601 term infants were identified from the PMMRC dataset and 614 term infants from the ANZNN dataset for the study period. The distribution of sex, birth weight, mode of birth, gestation, and plurality were similar between the two datasets. However, there was a difference in the numbers by year of birth. ANZNN demonstrated a trend towards more infants over time consistent with greater use of TH. However, PMMRC demonstrated a stable proportion of infants receiving TH.ConclusionThe combined data enabled an estimate to be made of the total NE burden nationally. Moderate and severe NE was documented over the epoch using the consistent PMMRC criteria but the additional ANZNN data illustrated infants cooled outside of moderate to severe NE. The two datasets were definitely not interchangeable for the purpose of NE case ascertainment. There were no major differences demonstrated in the receipt of TH when analysed by ethnicity.